Raft & Diving And Climbing Strategies On Students’ Motivation In Writing - Minda, Sri (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2019)
This research attempted to investigate whether teaching strategies significantly affect the students’ motivation in writing and the problems which students face during the implementation the strategies. The strategies were RAFT (Role, Audience, Format, and Topic) and Climbing and Diving. This research deals with the experimental research design. The population of this study was the students of the first year of Intensive language learning programme IAIN Padangsidimpuan. The instruments used were questionnaire and interview. The questionnaire sheet was designed with Likert scale. Through t-test calculation it was found RAFT strategy significantly affect the students’ motivation in writing. It also found that Climbing and Diving strategy significantly affect the students’ motivation in writing. The problems which students face during the implementation of RAFT and Climbing and Diving strategies in writing expository are: a. RAFT does not provide enough; b. RAFT strategy only helps students to pass choosing topic and drafting which are parts of pre-writing; c. Climbing and Diving strategy does not always give students enough time to write the drafts because of the limited time; d. Students may lose control in writing because the is no certain pattern of this strategy.